PENENTUAN ISI AWAL MINYAK DITEMPAT DENGAN MENGGUNAKAN METODEMATERIAL BALANCE DAN VOLUMETRIK PADA RESERVOIR ADZ - Dikky Fathurochman Sidiq; Lestari Said (President University, 2018)
Determination of the initial oil content of a reservoir starts from exploration activities. In the initial stage, the determination of the initial oil reserves is determined. This aims to determine whether the project can be profitable for the company or not. Over time the determination of the initial contents of the oil continues to be carried out to improve the accuracy of calculations using the material balance method.In the reservoir